FACTORS CONTRIBUTING TO MEDICATION ERRORS IN PRESCRIPTION READING AT THE PHARMACY OF THE HOSPITAL X - Yuristi Mahardika, Yesika; Suryanto; Rozany, Farida (Universitas Brawijaya, 2025)
Medication error is a mistake in the prescribing process and a failure in the treatment process that has the potential to cause harm and can endanger patients. During the year 2024, 22 medication errors were found in the pharmacy department of Hospital X. Therefore, this study aims to identify the causes of the high incidence of medication errors in the outpatient pharmacy department of Hospital X. This research uses qualitative methods. Data were obtained from primary data through interviews and Focus Group Discussions with 10 informants. Interviews were conducted with the head of the pharmacy installation along with the pharmacy staff, the outpatient installation, and the director. In contrast, the FGD was conducted with the director, the head of the medical support field, and the head of the pharmacy installation. Next, the data is grouped based on themes. After that, root cause analysis is used to determine the main cause. The study results revealed 7 main factors influencing the high rate of medication errors, namely the lack of implementation of electronic prescriptions, causing doctors to still write manual prescriptions, overprocessing during input by pharmacy staff, incorrect screening and input by pharmacy staff, many new pharmacy staff, insufficient human resources in the pharmacy installation, and pharmacy staff who tend to hesitate and fear when making confirmations. The analysis results show that the main cause of medication errors is the lack of implementation of electronic prescriptions, while the use of manual prescriptions complicates the pharmacists' ability to interpret them. After the implementation of electronic prescriptions at Hospital X, the IKP rate became 0 (no incidents occurred) during the observation period. Research shows that medication errors often occur because pharmacy staff find it difficult to interpret prescriptions from doctors who still use manual prescriptions. Electronic prescriptions need to be implemented immediately, with the preparation of a time schedule, the system and procedures to be used, as well as socialization for doctors.